2018
DOI: 10.1002/ehf2.12375
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic stress test echocardiography in patients with suspected heart failure with preserved ejection fraction: a pilot study

Abstract: AimsThe purpose of this pilot study was to assess the potential usefulness of diastolic stress test (DST) echocardiography in patients with suspected heart failure with preserved ejection fraction (HFpEF).Methods and resultsPatients with suspected HFpEF (left ventricular ejection fraction ≥ 50%, exertional dyspnoea, septal E/e′ at rest 9–14, and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) at rest < 220 pg/mL; n = 13) and a control group constituted from asymptomatic patients with arterial hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
2
23
0
3
Order By: Relevance
“…This study agrees with our findings that showed usefulness of diastolic stress echocardiography in discovering HFpEF patients in the individuals with dyspnea on exertion in simple clinical settings [48], without the use of right heart catheterization and comprehensive blood gas analysis.…”
Section: Clinical Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…This study agrees with our findings that showed usefulness of diastolic stress echocardiography in discovering HFpEF patients in the individuals with dyspnea on exertion in simple clinical settings [48], without the use of right heart catheterization and comprehensive blood gas analysis.…”
Section: Clinical Studiessupporting
confidence: 93%
“…However, only a small portion have been devoted to sex-related changes [7,47]. Our study group has recently published data regarding the diagnosis of HFpEF using diastolic stress echocardiography testing, which also partly illuminates the hemodynamic changes typical of HFpEF [48].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The parameters that have been studied most often, during or immediately after exercise, are the mitral E/e ′ ratio and the TR peak velocity, which indicate increases in mPCWP and PASP, respectively. 28,41,[244][245][246][247][248]250 Ideally a semi-supine bicycle test with imaging during exercise, or else a treadmill or upright bicycle exercise protocol with imaging at or immediately after peak stress, is recommended 41,244 but there are no universally adopted protocols. The European Association of Cardiovascular Imaging and the American Society of Echocardiography recommend a stepped protocol, starting at 25 W at 60 r.p.m.…”
Section: Exercise Stress Echocardiography: the Diastolic Stress Testmentioning
confidence: 99%
“…Acquiring echocardiographic data during exercise can unmask LV diastolic and systolic dysfunction. The parameters that have been studied most often, during or immediately after exercise, are the mitral E / e ′ ratio and the TR peak velocity, which indicate increases in mPCWP and PASP, respectively 28 , 41 , 244–248 , 250 …”
Section: Calculating and Interpreting The Hfa–peff Scorementioning
confidence: 99%
“…3,4 Studies have demonstrated the diagnostic utility of diastolic stress testing in identifying patients with cardiac dyspnea and HFpEF. 5 Prior studies have also shown that impaired exercise hemodynamics are associated with adverse cardiovascular outcomes. [6][7][8] However, current guidelines cite lack of sufficient evidence to determine the prognostic value of DD uncovered during stress testing.…”
mentioning
confidence: 99%